Reading Practices and Perceived Speaking Development among Indonesian EFL Undergraduates - Asti Gumartifa; Indah Windra Dwie Agustiani (ITScience (Information Technology and Science), 2026)
Reading provides sustained language input and may support the lexical resources needed for communication, yet university students increasingly encounter English through mixed print and digital sources. Objective of this study is to describe Indonesian English education undergraduates’ reading practices and examined how those practices were perceived to contribute to speaking development. 52 students from the first and final semesters of an English education study program participated in a descriptive mixed-data approach. A four-item reading-practices questionnaire, classroom interviews, and accessible speaking class records were used to gather data. Questionnaire responses were calculated using frequencies and percentages, while interview notes were used to interpret patterns without making causal claims. As a result, most participants liked English reading to some extent, but regular book reading was limited. Comics were also the most frequently selected material (28.8%), followed by novels and course books (23.1% each). Half of the students reported reading English books much less frequently (46.2%), whereas only 5.8% read daily. Although 51.9% reported that English texts were generally understandable, students with comparatively stronger speaking performance did not consistently report reading books frequently. This study claims that students perceived speaking development emerged from the interaction of various literacy and communicative practices rather than from book-reading frequency. Books remained a relevant source of vocabulary and language patterns, but the contribution depended on learners noticed, recycled, and activated the acquired language through speaking practice. Social media, online articles, audiovisual materials, and everyday communication expanded the sources from which students constructed the speaking resources. Therefore, it is cannot be claimed that reading is unrelated to speaking, but reading contributes indirectly and conditionally within a broader multimodal input, interaction, and output process